(untitled) (Jurnal SPEKTRUM, 2025)
Indonesia is currently in a transition toward clean energy. Therefore, accelerating the adoption of Electric Vehicles (EVs) as a replacement for fossil-fueled vehicles has become a strategic step that is being actively promoted. To support this, the availability of adequate infrastructure is a key factor, with charging stations serving as the main infrastructure for electric vehicles. For optimal operation, the development of charging stations requires proper location selection and design. This study focuses on the design and location selection of Public Electric Vehicle Charging Stations (SPKLU) intended for electric motorcycles in the South Bali region. The design features a three-dimensional model of the charging station, along with its corresponding electrical plan. Meanwhile, location selection is carried out using the Analytical Hierarchy Process (AHP) method by evaluating potential sites. The outcome of this study is the identification of the best location for installing the SPKLU, accompanied by design suited to the site’s characteristics and the SPKLU’s electrical design. It is expected that this work can serve as a study and reference for further development to accelerate the adoption of electric vehicles in Bali.